Analisis Perhitungan Pajak UMKM dengan PP 55 Tahun 2022 - Laily, Aulia Najmi; Diarany Sucahyati (AKUNTANSI 45, 2024)
Taxes play an important role in the life of a country, especially in Indonesia. This tax is used to achieve goals such as development, state interests, and economic regulation in Indonesia. Therefore, as an Indonesian citizen, LG also participated as a Private Taxpayer in making its tax payments. Because LG will report tax payments, researchers assist KKP EDS in filling out SPT OPs, where SPT OP itself has 3 types of E-Forms, including 1770, 1770S, and 1770SS. LG itself is a free worker who will use e-Form 1770. In this e-Form, there is an appendix in the form of PP23/PP55 which is the PPh Final in accordance with PP No. 55 of 2022, which states that the gross income in a year if it reaches Rp500,000,000.00 in a year, therefore researchers explained that LG's income subject to the PPh Final is 0.5% . Therefore, the result of this research is that LG will be subject to the PPh Final starting from September to December because LG's gross income has reached Rp500.000.000 in August and September will be subject to the PPh Final.